TNF-α and IL10 gene polymorphisms in women with postmenopausal osteoporosis. (April 2016) - Kotrych, Daniel; Dziedziejko, Violetta; Safranow, Krzysztof; Sroczynski, Tomasz; Staniszewska, Marzena; Juzyszyn, Zygmunt; Pawlik, Andrzej
Abstract: Objective: Postmenopausal osteoporosis is a common disorder characterized by decreased bone mineral density (BMD). Proinflammatory cytokines are among the significant factors involved in bone turnover. They are the stimulants of bone resorption, acting directly on osteoclasts and osteoclast precursors. In this study, we examined the TNF-α (−308G>A) (rs1800629) and IL10 (−1082G>A) (rs1800896), (−592C>A) (rs1800872) polymorphisms in postmenopausal women with BMD T -scores less than and greater than or equal to −2.5 SD. Study design: This study included 224 postmenopausal women with BMD T -scores lower than −2.5 SD (mean: −3.02 ± 0.53) and 238 postmenopausal women with BMD T -scores −2.5 SD and greater (mean: −1.33 ± 0.51). Results: There was a decrease in the frequency of IL10 1082 G allele carriers (GG and GA genotypes) in women with T -scores below −2.5 SD (GG + GA vs AA: OR = 0.65, 95% CI = 0.44−0.97, p  = 0.037). With regard to the TNF-α −308 G>A polymorphism, in the women with T -scores below −2.5 SD, the increased frequency of GG homozygotes and G allele carriers was detected (AA + GA vs GG: OR = 0.54, 95% CI = 0.35−0.82, p  = 0.004). Conclusions: The results of our study suggest an association between TNF-α −308G>A and IL10 −1082G>A polymorphisms and postmenopausal osteoporosis.